Investigating Code Mixing as a Feature of Bilingualism in Indonesian Language Education - Novarisa, Krisna; Sari, Lusi Komala; Mgbemgasha Apakama, Lusi (Paidea : Jurnal Pendidikan dan Pembelajaran Indonesia, 2025)
In the teaching and learning process, Indonesian is formally used as the language of instruction. However, students frequently incorporate regional or foreign languages during classroom interactions, both within and beyond the classroom context, often without regard for the appropriateness of the language variety used. For students, the primary concern is that the intended message is conveyed and understood. This study aims to examine the forms of code mixing and identify the factors that influence its occurrence in Indonesian language learning among seventh-grade students at State Junior High School 2 Bangko Pusako, Rokan Hilir Regency. Employing a qualitative case study approach, data were collected through non-participant observation of classroom conversations. The findings indicate the presence of code mixing during the learning process, with two types identified: inner code mixing (27 instances) and outer code mixing (7 instances). The factors contributing to code mixing include role identification (1 instance), interlocutor (1 instance), language function and purpose (9 instances), and speaker-related factors. These findings highlight the linguistic dynamics in multilingual classrooms and suggest a need for pedagogical strategies that acknowledge and manage students' bilingual or multilingual practices.